2021
DOI: 10.4314/gmj.v55i2.8
|View full text |Cite
|
Sign up to set email alerts
|

Improving stroke care in Ghana: a roundtable discussion with communities, healthcare providers, policymakers and civil society organisations

Abstract: Even though there have been advances in medical research and technology for acute stroke care treatment and management globally, stroke mortality has remained high, with a higher burden in low- and middle-income countries (LMICs) such as Ghana. In Ghana, stroke mortality and disability rates are high, and research on post-stroke survival care is scarce. The available evidence suggests that Ghanaian stroke survivors and their caregivers seek treatment from pluralistic health care providers. However, no previous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…Community-based rehabilitation includes the social and family support in rehabilitation, which in turn, provides the necessary physical, emotional and spiritual support needed by the patient (Wasti et al 2021). This study as well as that of Sanuade et al (2021) recommend the introduction of home and community-based stroke rehabilitation in Ghana to help minimise the complications of stroke as well as to reintegrate patients back into their previous life.…”
Section: Discussionmentioning
confidence: 86%
See 3 more Smart Citations
“…Community-based rehabilitation includes the social and family support in rehabilitation, which in turn, provides the necessary physical, emotional and spiritual support needed by the patient (Wasti et al 2021). This study as well as that of Sanuade et al (2021) recommend the introduction of home and community-based stroke rehabilitation in Ghana to help minimise the complications of stroke as well as to reintegrate patients back into their previous life.…”
Section: Discussionmentioning
confidence: 86%
“…Therefore, stroke patients in these facilities did not have access to the services of these HCPs showing a limitation in their rehabilitation, which could affect their outcome as also reported by Ameh et al (2017). Similar studies conducted in Ghana revealed the unavailability of some HCPs for stroke rehabilitation especially the allied health professionals, which included occupational therapists, speech therapists and clinical psychologists (Baatiema et al 2017b;Sanuade et al 2021; names deleted to maintain the integrity of the review process).…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Ghana has a vibrant pluralistic healthcare system made up of both mainstream biomedical (conventional) and complementary (herbal) health systems, which are all involved in stroke care and rehabilitation ( 59 ). In many rural and semi-urban areas in Ghana, most patients with stroke tend to use complementary medicine treatment either exclusively or in parallel with conventional medicine ( 40 , 60 ) for varied reasons ranging from faith and cultural congruence to accessibility, cost, and belief that these approaches are safe ( 40 , 61 , 62 ).…”
Section: Discussionmentioning
confidence: 99%